The development and psychometric evaluation of COVID-19 staff questionnaire for infectious disease outbreak readiness and preparedness (SQIDORP) - Yangama Jokwiro; Tracy Urbanavicius; Ainsley M. Robinson; Cathy Scott; Md Rafiqul Islam (BMC, 2022)
Abstract Background The COVID-19 pandemic has inundated the capacity of hospitals across the globe, exhausting resources, and placing extreme burden on health care workers (HCWs). Hospital preparedness during infectious disease outbreak involves development and implementation of appropriate strategies, procedures, and adequate training for HCWs. Reliable and valid tools to evaluate the perception of HCWs on the effectiveness of hospital preparedness strategies are imperative and literature is yet to fill that gap. Methods Items for 'The Staff Questionnaire for Infectious Disease Outbreak Readiness and Preparedness (SQIDORP)' were selected from literature that addressed hospital preparedness during novel pandemic outbreaks. The SQIDORP was distributed within a regional hospital in Victoria, Australia. Psychometric evaluation included estimates of reliability and factor analysis while factors associated with the questionnaire were explored using regression analysis. Results Omega coefficient of 0.89, Cronbach's alpha coefficient of 0.88 and item-total correlations (> 0.3) indicated adequate reliability of the SQIDORP. Factor Analysis yielded three meaningful latent factors that are effectiveness of training (Factor 1), self-confidence (Factor 2) and risk to self and stress (Factor 3). Demographic factors did not influence the correlation with SQIDORP. However, rating 'the current plan for management of COVID-19 in your ward' and 'personal knowledge/skills in caring for patients with COVID-19' had significant positive correlation and accounted for 33% of the variance in readiness and preparedness using SQIDORP (R2 = 0.33, F = 10.227, P < 0.001). Conclusion Most of the items of SQIDORP questionnaire achieved adequate internal consistence reliability. This is a valuable tool that can be utilized by hospitals to explore aspects of preparedness and give insights to the knowledge, skills, and mental health of HCWs, as perceived by the HCW themselves.